Hyper‐CVAD plus ponatinib versus hyper‐CVAD plus dasatinib as frontline therapy for patients with Philadelphia chromosome‐positive acute lymphoblastic leukemia: A propensity score analysis. Issue 23 (1st August 2016) - Sasaki, Koji; Jabbour, Elias J.; Ravandi, Farhad; Short, Nicholas J.; Thomas, Deborah A.; Garcia‐Manero, Guillermo; Daver, Naval G.; Kadia, Tapan M.; Konopleva, Marina Y.; Jain, Nitin; Issa, Ghayas C.; Jeanis, Vicki; et al.
Abstract : BACKGROUND: The clinical efficacy of hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone (HCVAD) plus ponatinib has not been compared with that of HCVAD plus dasatinib in patients with Philadelphia chromosome‐positive acute lymphoblastic leukemia (Ph+ ALL) in a randomized clinical trial. METHODS: The authors analyzed 110 patients with newly diagnosed Ph+ ALL who were enrolled in 2 consecutive, prospective, phase 2 clinical trials of frontline HCVAD with either dasatinib (63 patients) or ponatinib (47 patients). Propensity score analysis with 1:1 matching with the nearest neighbor matching method and inverse probability of treatment weighting (IPTW) analysis based on the propensity scores were performed to assess response rates, event‐free survival (EFS), and overall survival (OS) between the cohorts. RESULTS: Propensity score matching identified 41 patients in each cohort. With propensity score matching, the 3‐year EFS rates for patients treated with HCVAD plus ponatinib and HCVAD plus dasatinib were 69% and 46%, respectively ( P =.04), and the 3‐year OS rates were 83% and 56%, respectively ( P =.03). IPTW analysis using prematching cohorts demonstrated that patients treated with HCVAD plus ponatinib had significantly higher rates of minimal residual disease negativity by flow cytometry on day 21, complete cytogenetic response at complete response, major molecular response at complete response and at 3 months, and complete molecular response at 3 months. IPTW confirmed that treatment with HCVAD plus ponatinib was associated with longer EFS ( P =.003) and OS ( P =.001) compared with treatment with HCVAD plus dasatinib. CONCLUSIONS: The clinical outcome of patients treated with HCVAD plus ponatinib appears to be superior to that of patients treated with HCVAD plus dasatinib among individuals with Ph+ ALL. Cancer 2016;122:3650‐6. © 2016 American Cancer Society . Abstract : Propensity score analysis using 2 prospective, phase 2 clinical trials demonstrated that the clinical outcome of treatment with hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone plus ponatinib appears superior to that of the same combination plus dasatinib in patients with Philadelphia chromosome‐positive acute lymphoblastic leukemia.